Exploring the Link Between Food-Hygiene Practices and Diarrhoea Among the Children of Garments Worker Mothers in Dhaka (Anwer Khan Modern Medical College Journal, 2011)
A cross-sectional study was conducted to investigate the potential factors of food-hygiene practices of mothers on the prevalence of diarrhoea among their children. Mothers who had children aged 6 months–5years were recruited in a Garments factory in Dhaka, Bangladesh. The food-hygiene practices included hand-washing, method of washing utensils, separation of utensils for raw and cooked food, and the location where foods were prepared for cooking. A face-to-face interview was conducted, and data on 206 mothers were analyzed. The risk of diarrhoea was significantly higher among children whose mothers prepared food without proper neatness and kept the food to be fed by the children throughout the following day, compared to children whose mothers prepared and preserved food hygienically. (adjusted odds ratio=2.85, 95% confidence interval 1.11-7.28). The results indicate that food-hygiene practices of mothers, such as preparing food with neatness and preserving consciously has a potential impact in preventing diarrhoea among children of garments working mothers. Key words: Cross-sectional Studies; Diarrhoea; Infantile; Food Handling; Hygiene; Knowledge; Attitudes and Practice DOI: 10.3329/akmmcj.v1i2.7458 Anwer Khan Modern Medical College Journal 2010; 1(2): 04-11